HUBUNGAN TINGKAT KECEMASAN DENGAN MEKANISME KOPING PADA PASIEN GAGAL JANTUNG KONGESTIF DI IRINA F BLU RSUP Prof. Dr. R.D. KANDOU MANADO - Djoni Ransun; Joke Pijoh; Esrom Kanine (Jurnal Ilmiah Perawat Manado (Juiperdo), 2013)
Anxiety in patients with Congestive Heart Failure caused because they experience shortness of breath and chest pain so they tend to be restless . Anxiety can motivate individuals to adapt to stressors and taking appropriate action to address them . Coping mechanism is the result of individual actions in the face of stressors . When an individual is able to face the stressor well will produce adaptive coping whereas when individuals are not able to find a good way out then will perform a maladaptive coping . This study aims to determine the relationship of the level of anxiety with coping mechanisms in patients with CHF. Descriptive research study Irina F analitik.Tempat heart , study time juni 2012 with accidental sampling technique on 30 responden.Instrumen anxiety questionnaires and questionnaires HRS - A COPE coping mechanisms. Chi Square analysis results found a significant relationship between the level of anxiety with coping mechanisms in CHF patients ( p = 0.004 < α = 0.05 ) OR = 12 Conclusion CHF patient anxiety levels shown to be associated with coping mechanisms whereby 12x experiencing mild anxiety level than the level of adaptive coping moderate anxiety. Suggestion: increase understanding of CHF patients need attention and support from family , and health practitioners in order to improve the coping mechanisms